Relationship of Organic Content in Sediment with Morphometric Mangrove Leaves (Rhizophora apiculata) in the West Mangrove Ecosystem, Dumai City, Riau Province - Mia Audina; Sofyan Husein Siregar; Bintal Amin (Faculty of Fisheries and Marine, Universitas Riau, 2021)
The damage rate of mangrove forests in Indonesia is considered as the fastest and largest in the world. The reduced density of mangroves can be influenced by the water quality and the organic matter content around the mangrove ecosystem, causing changes in the mangrove leaves both in the shape of the length and width. This study was conducted in the mangrove ecosystem in the western part of Dumai City, with the aim of determining the morphometric size of the leaves of Rhizophora apiculata and its relationship with the content of organic matter in the sediment. The method used in this study was survey method, where observations and sampling were performed directly in the field and some of samples were analyzed in the laboratory. Mangrove density obtained from the research results ranges from 1966.66 - 4700 ind/ha, organic matter content 10.88 -17.21%. The morphometric size of the leaf length varies from 13.03 - 15.05 cm, the leaf width varies from 4.65 - 5.42 cm, and the length of the petiole varies from 1.59 - 1.91 cm. There is no significant relationship between the mangrove leaf morphometric with sediment organic matter in the studied area.